HER2-Specific Pseudomonas Exotoxin A PE25 Based Fusions: Influence of Targeting Domain on Target Binding, Toxicity, and In Vivo Biodistribution; Pharmaceutics; Vol. 12, iss. 4 - Ding H. Haozhong; Altai M. Mohamed; Wen Yin; Lindbo S. Sarah; Hao Liu; Garousi J. Javad; Tianqi Xu; Orlova A. M. Anna Markovna; Ficai A. Anton; Tolmachev V. M. Vladimir Maksimilianovich; Hober S. Sophia; Gräslund T. Torbjörn (2020, 2020)
Title screen